Evaluasi Mutu Sarana dan Prasarana Polri untuk Pengamanan Objek Vital dalam Rangka Pengamanan Pemilu 2024: Pengamanan Objek Vital dalam Rangka Pengamanan Pemilu 2024 - Raslin, Harvin; Astuti, Septi; Saragih, Agung Shamsudin; Wahyono, Ary; Priyotomo, Gadang (Pusat Penelitian dan Pengembangan Polri, 2024)
The Directorate of Vital Object Security (Ditpamobvit) of the Indonesian National Police is responsible for securing vital objects by applying predictive policing techniques to anticipate and analyze issues that could potentially disrupt public security. As the 2024 elections approach, readiness for securing vital objects becomes crucial to preempt potential security disturbances. This study aims to analyze the preparedness of facilities and infrastructure in supporting the performance of Ditpamobvit. The methodology employed is descriptive-analytical with both qualitative and quantitative approaches, using interviews, observations, checklists, and questionnaires. The results indicate that Pamobvit facilities at the Polda level are generally adequate and function well according to regional needs, whereas at the Polres level, they are still limited. Regular training is necessary to enhance personnel knowledge, storage facilities are available but not yet sufficient, and skill improvement is undertaken through both internal and external training. However, high-tech training needs to be optimized, training for modern facilities ceases after contract periods, maintenance costs lack standard indices at SBK Polri, there is no budget support for operator welfare, new facilities do not keep up with the increase in vital objects, personnel understanding of incident handling is limited, and there is a lack of special storage space. Required solutions include optimizing high-tech training, extending training for modern facilities, establishing maintenance cost norms, securing budget support for operator welfare, planning new facility procurement, improving understanding through simulations, and providing accessible standard operation guides.